You wouldn`t let your phone run out of battery: an interpretative phenomenological analysis of male professional football coaches` well-being - Higham, A. J.; Newman, J. A.; Rumbold, J. L.; Stone, J. A. (Qualitative Research in Sport, Exercise and Health, 2023)
Little is known about how coaches make sense of and experience well-being within their given context as athletes have traditionally been at the forefront of well-being research, which is concerning given coaches are as susceptible to well-being challenges. Considering well-being and coaching comprise of many idiosyncratic and sociocultural interactions, the present study employed a combined bioecological and interpretative phenomenological analysis (IPA) approach to explore how six professional football coaches make sense of and experience well-being within the context of football clubs. Due to IPA`s contextualist position, commitment to the individual, and ability to empower and give voice, two group experiential themes were created: `The endeavour to comprehend coaches` well-being`, and `Volatility of the football coaching profession: fragmented well-being`. Findings showed that football coaches made sense of their well-being by drawing on past playing experiences and sociocultural interactions, with some coaches comprehending well-being as a physical and mental battery. Additionally, several coaches experienced a fragmentation of self and subsequent well-being due to conflicts within and between their ecological niche. A combined bioecological and IPA approach facilitated and enriched how well-being was contextually made sense of and experienced.